Influence of Obstructive Sleep Apnea on Systemic Inflammation in Pregnancy - Alonso-Fernández, Alberto; Ribot Quetglas, Caterina; Herranz Mochales, Andrea; Álvarez Ruiz De Larrinaga, Ainhoa; Sánchez Barón, Andrés; Rodríguez Rodríguez, Paula; Gil Gómez, Ana Victoria; Pía Martínez, Carla; Cubero Marín, José Pablo; Barceló Nicolau, Maria; Cerdà Moncadas, María; Codina Marcet, Mercedes; et al. (Frontiers in Medicine, 2021)
Background: Obstructive sleep apnea (OSA) is prevalent in pregnancy and it is associated with adverse pregnancy-related outcomes such as gestational diabetes, preeclampsia, and low birth weight. Maternal systemic inflammation is proposed to be one of the main intermediate mechanisms. However, the effects of OSA on systemic inflammation are unknown in normal pregnancy. Methods. Women in the 3rd trimester underwent hospital polysomnography to evaluate whether OSA increases systemic inflammation in normal pregnancy and its potential association with adverse fetal outcomes. OSA was defined as an apnea–hypopnea index (AHI) of ≥ 5 h-1. Plasma cytokines levels (TNF-α, IL-1β, IL-6, IL-8, and IL-10) were determined by multiple immunoassays. Results. We included 11 patients with OSA and 22 women with AHI<5 h-1, who were homogeneous in age, and body mass index (BMI). Women with OSA had significant higher levels of TNF-α, IL-1β, IL-8, and IL-10. We found significant correlations between AHI during REM and TNF-α (r=0.40), IL-1β (r=0.36), IL-6 (r=0.52), IL-8 (r=0.43), between obstructive apnea index and TNF-α (r=0.46) and between AHI and IL-1β (r=0.43). We also found that CT90% was related to IL-8 (r=0.37). There were no significant differences in neonatal characteristics; however, we found inverse correlations between TNF-α and IL-8 with birth weight (both r=-0.48), while IL-8 showed a significant inverse relationship with neonatal gestational age (r=-0.48). Conclusions. OSA in our normal pregnancy population was associated with higher systemic inflammation, which was related to obstructive events, especially during REM sleep. Moreover, systemic inflammation was inversely correlated with neonatal birth weight and age.